Paglibán at Iba Pang Tula - Inojosa, J.E. (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
“Paglibán at Iba Pang Tula” are demonstrations of what defines “paglibán” or “moving across.” The poems attempt to interrogate various navigations (land, sea, river, city) and are an assortment of emotions and insights borne by such journeys. The poems explore these navigations through a mixture of traditional (sestina, diona) and contemporary (free verse, prose poetry) forms while mapping what appears to be disjunct but actually adjunct experiences of a wandering and tentative persona. For some of the poems, the origin and the horizon are clear (“Paglibán,” “Magaspang na Salin ng Artikulo 429 ng Kodigo Sibil,” “Liwaliw sa Siargao”). However, when the persona reaches the city, their unsettled unease becomes more apparent (“Baclaran,” “Matandang Balara”) but eventually settles in the possibility of rest (“Cubao, Kinabukasan”). In general, the collection not only traverses places and experiences but their concurrent concourse and conflict.